Peran Pemerintah Desa terhadap Penanganan Stunting di Desa Batu Belanak Kecamatan Suak Midai Tahun 2021-2023 - Dela Pusfita; Kustiawan Kustiawan; Eki Darmawan (Jurnal Media Administrasi, 2024)
Stunting in Batu Belanak Village has been widespread since 2023. There are three villages in Suak Midai District, these three villages are Batu Belanak Village which holds the highest ranking for stunting problems. Batu Belanak village has 7 stunted children, 4 people in Gunung Jambat village and 6 people in Air Kumpai village. Therefore, there needs to be a responsible role for the village government in this matter. The aim of this research is to find out how the Village Government handles stunting in Batu Belanak Village. This research uses a qualitative approach method. Data collection techniques include observation, interviews and documentation. This research uses according to Ryas Rasyid which consists of the Government's Role as Regulator, the Government's Role as Dynamisator, and the Government's Role as Facilitator. The results of the findings are that the role of the village government in handling stunting is carried out by the village government is quite good, both from the role of the Government as a Regulator, the Village directs it to socialize with the community so that it becomes better. The government has added a program for stunted children in the form of vitamins. The role of the Government as a village government dynamist provides good new innovations. Findings for the role of the dynamist include the community not being timely when there is socialization. The government's role as a facilitator is quite good and appropriate in handling stunting in Batu Belanak village.